Poetry Body & Chords: Alternatives to Art in Mato Grosso’s Hinterland - Almeida Barbosa, Everton; Mendes de Melo, Álvaro (Guará Journal, 2019)
This article intends to present the extension project, titled Poesia Corpo & Cordas, which is associated to the undergraduate course of Languages in the University of Mato Grosso State, Tangará da Serra campus, in its social role in the campus and in the city. The project, which has been in operation since 2014, initially aimed to implement a cultural repertoire that is alternative to what is commonly offered in mass media, at parties and local events, and aims to serve both an audience that already seeks different artistic manifestations and to sensitize new public to the Brazilian cultural diversity. Over the course of 4 years, other activities were proposed according to the local demands and skills of members and collaborators that were emerging. It is included, as an important aspect of the work’s evolution, an approximation with the universe of Basic Education.